Synergistic antitumor efficacy of aspirin plus lenvatinib in hepatocellular carcinoma via regulating of diverse signaling pathways - Yan, Xijing; Yu, Haoyuan; Liang, Jinliang; Hu, Zhongying; Li, Xuejiao; Liu, Huanyi; Yao, Jia; Sui, Xin; Zheng, Jun; Li, Rong (Cell death discovery, 2023)
It has been established that monotherapy yields limited efficacy in treating hepatocellular carcinoma (HCC), especially advanced HCC. Increasing evidence from preclinical studies and clinical trials indicates that combining multiple drugs can potentially refine treatment efficacy. Accordingly, it is crucial to explore more effective clinically feasible combination therapies to enhance the treatment outcomes of HCC patients. This study evaluated the antitumor efficacy and safety of combination therapy involving aspirin and lenvatinib in HCC. Through in vitro and in vivo assays, we demonstrated that this combination yielded stronger antitumor effects compared to lenvatinib or aspirin monotherapy. Furthermore, no significant adverse events were observed in an HCC mouse model during treatment. Mechanistic studies revealed that aspirin plus lenvatinib could target multiple oncogenes and tumor suppressors, affecting diverse signaling pathways in various biological processes conducive to antitumor effects. Overall, our findings suggest that aspirin plus lenvatinib could serve as a promising combination regimen to improve the therapeutic outcomes of HCC.